The association of cell adhesion molecules and selectins (VCAM-1, ICAM-1, E-selectin, L-selectin, and P-selectin) with microvascular complications in patients with type 2 diabetes: A follow-up study - Siddiqui, Khalid; George, Teena P.; Mujammami, Muhammad; Isnani, Arthur; Alfadda, Assim A. (Frontiers in Endocrinology, 2023)
Objective Chronic hyperglycemia induces pathogenic changes in the vascular endothelium and leads to the development of microvascular complications in patients with type 2 diabetes mellitus. Early identification of markers of diabetes complications may help to minimize the risk of the development and progression of microvascular complications. Methods This follow-up study was conducted in type 2 diabetic cohort aged between 30-70 years. Out of 160 eligible participants, 70 of them completed follow-up. Levels of cell adhesion molecules and selectins (VCAM-1, ICAM-1, E-selectin, L-selectin and P-selectin) at baseline and follow-up were measured using Randox Evidence biochip analyzer (UK). Development of microvascular complications (diabetic neuropathy, retinopathy and nephropathy) was evaluated. Results During the follow-up (2 years, median), 31 (44.3%) developed diabetic neuropathy, 10 (14.3%) developed diabetic retinopathy and, 27 (38.6%) developed diabetic nephropathy. A significant difference in levels of cell adhesion molecules and selectins were found in type 2 diabetic patients with and without microvascular complications. Multiple logistic regression analysis reveals that baseline level of VCAM-1 is significantly associated with microvascular complications; diabetic neuropathy(p=0.028), retinopathy (p=0.007) and nephropathy(p=<0.001). Additionally, levels of P-selectin (p=0.05) and L-selectin (p=0.008) is associated with diabetic nephropathy while retinopathy associated with L-selectin (p=0.005) only. Conclusion Cell adhesion molecules and selectins are indicators of microvascular complication among patients with type 2 diabetes (T2D). Association of these markers with the development of microvascular complications may provide additive information for developing strategies for diabetes management and prediction of microvascular complications.